202k views
2 votes
Solve for f: 6f + 9g = 3g + f

2 Answers

3 votes
Hi there!

• 6f + 9g = 3g + f

To solve for " f ". bring all th' like term together in the Eqn.

6f - f = 3g - 9g

5f = -6g

f =
\frac {-6}{5} g

~ Hope it helps!
User QuantStats
by
5.0k points
3 votes
Hi there!

Let's solve this equation step by step!
6f + 9g = 3g + f

To solve for f, we need to bring all the terms in the equation with an f in it to the left, and all the other terms (with a g) to the right.

First subtract f from both sides.
5f + 9g = 3g

Now subtract 9g from both sides.
5f = -6g

And finally divide both sides by 5.
f = (-6/5)g

Hence, your answer;

f = - (6)/(5) g

~ Hope this helps you!
User Clove
by
5.2k points